Avaliação do potencial antibiofilme e antimicrobiano de lectinas extraídas de organismos marinhos - Almeida, Alexandra Sampaio de (2023)
The biotechnological potential of marine organisms has been known since many centuries ago, where many of them were used in the treatment of various diseases, and over the years, several biologically active compounds have been isolated from these organisms. Among these compounds are lectins, which are proteins capable of recognizing and binding in a specific and reversible way to carbohydrates, and which have several biological applications such as antimicrobial activity and inhibition of bacterial biofilm formation. Thus, lectins emerge as a viable and effective antimicrobial option. Biofilms are able to provide a “safe” environment for fish and shrimp pathogens to persist in aquaculture systems and, in addition, these biofilms may also contain human pathogens, generating a potential risk to public health. Thus, the objective of the present work was to scan the potential biological activities of lectins isolated from marine organisms (algae and invertebrates) against planktonic microorganisms and bacterial biofilm. Six lectins from marine organisms were used, four from red algae – AML, BTL, BSL, SFL and two from AFL and ALL sponges. And these lectins were tested against seven bacterial strains, two of which are ATCC (American Type Culture Collection) reference: Escherichia coli and Sthaphylococcus aureus and five belonging to the collection of microbial cultures Profa. Regine Vieira (CMRV): Streptococcus mutans, Salmonella ser. Brandeirup Lamap 18, Pseudomonas 246B, Vibrio parahaemolyticus 53, Vibrio alginolyticus 39. The fungal strain from the National Institute for Quality Control in Health - INQS (FIOCRUZ) Candida albicans and the CRMV Aspergillus niger collection was also used. Antibacterial minimum inhibitory concentration (MIC) and agglutination tests, antifungal tests, antibiofilm tests and lethality against artemia nauplii were performed. As a result, it was found that only the AFL and ALL sponge lectins showed satisfactory results in the MIC test, inhibiting the growth of Gram positive strains, while in the agglutination test all lectins were able to agglutinate several strains, with emphasis on BTL, AFL and ALL that agglutinated a greater amount, in the antifungal tests there was inhibition of the growth only of the filamentous fungus Aspergillus niger and the lectins AML, BSL, SFL, AFL and ALL were successful. In the antibiofilm tests, all lectins were capable of inhibiting the growth of the biofilm of some strain, with emphasis on AML, which inhibited the biofilm of all strains. Among the tested lectins, only AML and ALL reduced the biofilm of V. parahaemolyticus, this fact is relevant because this bacterium is one of the opportunistic pathogens that most affects shrimp culture and when in biofilm this risk is higher, thus compounds that inhibit this microorganism are important in aquaculture. In lethality tests, only SFL was toxic, so care must be taken with handling this lectin in some uses. In view of all that was found, we can say that lectins from marine organisms are powerful tools with antimicrobial and antibiofilm action that can be used in various activities, including aquaculture.